Creating incentives for petrochemistry development in sanctioned economy - V. Ya. Afanasiev; O. V. Baykova; O. I. Bolshakova; A. A. Romantsov (Вестник университета)
Under the conditions of sanctions, the development of petrochemical production in Under the conditions of sanctions, petrochemical production development in Russia is especially important both from the point of view of high-grade products growth with increased margins and the need to increase demand for hydrocarbons within the country with a decrease in export supplies.   The purpose of the study is to analyze the existing and identify the main possible incentive measures of state support to enhance investment activities in modernization and creation of new production facilities of Russian petrochemical complex.   Methods such as generalization, analysis and synthesis, classification and modeling were used in the work. As a study result, main problems and challenges facing the industry have been identified. Priority areas of oil and gas companies’ activity necessary for petrochemistry accelerated development, positive examples of cooperation in the field of gas processing and gas chemistry, as well as industrial clusters creation have been presented. Project financing mechanisms of the state corporation VEB.RF have been analyzed. The need to attract competent specialized Russian EPC contractors from the register recommended by VEB.RF for implementing projects in the field of petrochemistry has been explained. Using the example of methanol production and its use as a raw material for high-grade products creation, importance of long-term contractual relations between the state and business, such as agreements on protection and promotion of capital investments and special investment contracts, has been shown. The need to ensure continuity of state support measures at all stages of creating and implementing technologies for developing and improving petrochemical products has been formulated.